Kan man genom kartstudier förutse häckningsframgång för ängshök (Circus pygargus) i Uppland? - Litsgård, Fredrik (SLU/Dept. of Ecology, 2008)
Montagu´s harrier (Circus pygargus) is a diurnal, Eurasian raptor, which migrates from its northern breeding grounds to winter in sub-Saharan Africa. In Sweden, its core breeding area is centred on the island of Öland, with a stable breeding population of approximately 40 pairs. The province of Uppland is on the northern end the distribution range, where 4-8 pairs have regularly bred since the 1980s.